2016
DOI: 10.1097/md.0000000000005561
|View full text |Cite
|
Sign up to set email alerts
|

Finding resiliency in the face of financial barriers

Abstract: Patients with chronic diseases often face financial barriers to optimize their health. These financial barriers may be related to direct healthcare costs such as medications or self-monitoring supplies, or indirect costs such as transportation to medical appointments. No known framework exists to understand how financial barriers impact patients’ lives or their health outcomes.We undertook a grounded theory study to develop such a framework. We used semistructured interviews with a purposive sample of particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
(22 reference statements)
1
13
0
Order By: Relevance
“…The fact that our overall exposure (at least one financial barrier) retained a significant positive association with disease-related hospitalization in spite of adjustment for income suggests that financial barriers may be relevant, at least for some aspects of chronic disease care, regardless of income level. Consistent with prior qualitative research [ 21 ], financial barriers appear relevant even for some patients with higher income and may not be experienced universally by those with lower income. This suggests that a patient’s perception of a financial barrier might be used in clinical and research settings as an additional measure along with standard measures of socioeconomic status (i.e.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The fact that our overall exposure (at least one financial barrier) retained a significant positive association with disease-related hospitalization in spite of adjustment for income suggests that financial barriers may be relevant, at least for some aspects of chronic disease care, regardless of income level. Consistent with prior qualitative research [ 21 ], financial barriers appear relevant even for some patients with higher income and may not be experienced universally by those with lower income. This suggests that a patient’s perception of a financial barrier might be used in clinical and research settings as an additional measure along with standard measures of socioeconomic status (i.e.…”
Section: Discussionsupporting
confidence: 82%
“…The observed associations for those with financial barriers is potentially mediated by cost-related non-adherence to medical therapies [ 5 , 6 ] and health behaviour modification [ 31 ], which result in poorer control of chronic diseases and ultimately culminate in hospitalizations and death. We recently completed a grounded theory study on this topic where we found that the impact of financial barriers on patients’ lives is determined by a complex set of individual patient and system factors [ 21 ]. The complexity of perceiving financial barriers as well as the demonstrable association with adverse outcomes and increased costs seen in this study may provide an impetus for policymakers to seek to invest in interventions which minimize the impact of financial barriers, such as copayment elimination [ 32 ], patient navigation [ 33 ] and patient self-advocacy education [ 34 ] — though the ultimate impact of these interventions remains inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work was embedded within a larger qualitative study focused on financial barriers to care, where data was collected from 34 participants with cardiovascular-related chronic diseases, which included both FN and non-FN individuals [30]. Within this larger study, among those with diabetes, we found compelling differences in the experiences reported by participants living in FN communities and non-FN participants.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the majority of these studies evaluating illness beliefs were conducted in an outpatient non-emergent setting. Financial insecurity may also account for this incongruence between disease beliefs and medication self-efficacy [ 26 , 27 ]. Even so, there was no significant discrepancy between incomes among those presenting with elevated BP compared to those presenting with normal BP.…”
Section: Discussionmentioning
confidence: 99%